Implementasi Total Quality Management (TQM) dalam Meningkatkan Sumber Daya Manusia (SDM) yang Bermutu di SMP Ash Shiddiqi Curahlele Jember - Tirza Hayatur Rohmah; Zainuddin Al Haj Zaini; Lailatul Usriyah (Instructional Development Journal, 2024)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving the quality of Human Resources (HR) at SMP Ash Shiddiqi Curahlele Jember for the 2023/2024 academic year. The method used in this research is descriptive qualitative, with data collection techniques including interviews, observations, and document studies. The results of the study show that the implementation of TQM in the HR field is carried out through three main stages: preparation, execution, and evaluation. Supporting factors, such as a strategic location and adequate facilities, contribute positively to the application of TQM, while inhibiting factors, such as students' attitudes of feeling underestimated, need to be addressed to ensure more effective learning processes.Through this research, it is expected that efforts to improve the quality of education at SMP Ash Shiddiqi Curahlele Jember will make a significant contribution to the development of qualified human resources. The findings of this study can also serve as a reference for other educational institutions in applying TQM principles to achieve better educational goals. Thus, the application of TQM not only focuses on improving the teaching and learning process but also creates an environment that supports the growth and development of students as competent and moral individuals.